Teacher-Student Relationship and Learning Motivation at SMP Muhammadiyah 5 Tulangan: Hubungan Guru-Murid dan Motivasi Belajar di SMP Muhammadiyah 5 Tulangan - Hariyanto, Noval Budi; Ansyah, Eko Hardi (Journal of Islamic and Muhammadiyah Studies, 2025)
General background: Motivation is a crucial factor influencing student learning outcomes, as it drives persistence and engagement in the classroom. Specific background: In Muhammadiyah schools, teacher-student relationships are assumed to play a central role in shaping students’ motivation, yet empirical evidence remains limited. Knowledge gap: While previous studies have explored external factors such as family or environment, fewer have examined how teacher-student relational quality contributes directly to students’ learning motivation in the Muhammadiyah context. Aims: This study investigates the relationship between teacher-student relationships and learning motivation among students at SMP Muhammadiyah 5 Tulangan. Results: Using a quantitative correlational design with 200 students selected from 338 through Slovin’s formula, data were collected via Likert-scale instruments and analyzed with Product Moment correlation. Normality and linearity tests met statistical assumptions, and the correlation analysis revealed a positive though weak association (r = 0.178, p < 0.05), with teacher-student relations explaining 3.2% of learning motivation variance. Novelty: The study expands prior research by situating the relational dynamics within Muhammadiyah education, offering insight into a psychosocial variable not often highlighted. Implications: Strengthening teacher-student relationships may serve as a practical pathway for fostering sustainable learning motivation in Islamic-based schooling. Highlights: Teacher-student relationship shows a positive correlation with motivation. Relational quality explains a small yet meaningful portion of variance. Novel contribution within Muhammadiyah educational settings. Keywords: Teacher-Student Relationship; Learning Motivation; Correlational Study; Junior High School; Muhammadiyah Education